UTILIZATION OF DISPOSED WASTE MATERIAL ON GREEN CONCRETE - Rukzon, Sumrerng; Chuponsat, Arthorn; Tansathit, Tiwa; Seesai, Prapat; Chindaprasirt, Prinya (Srinakharinwirot University Journal of Sciences and Technology, 2022)
This research investigates the development for using ground palm oil fuel ash (GPOFA) and recycle block aggregate (RCB) as a construction material. This work presents a study of the compressive strength, water absorption and flexural strength of concrete containing ground palm oil fuel ash (GPOFA) and recycle block aggregate (RCB). Portland cement (CT) was partially replaced with GPOFA of 20 and 40% by weight of the binder. The concretes of GPOFA and RCB with water cement ratio of 0.40 and 0.50 and RCB aggregate to CT+GPOFA (Binder) ratio of 2.00 and 3.00 were used in this work. Superplasticizer (SP) was used to improve the workability of concretes. The test results found that the concretes with low water absorption, good compressive and flexural strength were obtained with GPOFA of 20% by weight of the binder and water binder ratio of 0.40. In addition, the results indicated that the recycle block can be used as an aggregate in producing concrete with ratio of RCB aggregate to CT+GPOFA of 3.00.